The Current Situation of Territorial and Border Conflicts in Latin America and the Caribbean - Adela M. Alija (Comillas Journal of International Relations, 2019)
The main objective of this article is to review the current border and territorial conflicts in Latin America and the Caribbean, as well as their importance in the American scenario. To better understand the current situation it is necessary to review its background, highlighting its complexity. At present many American countries have differences related to their territory. In some cases, cross-border crises between countries have involved military force. These conflicts are recurrently revived by the governments that use them as an element of national cohesion at certain times, as an element of distraction from other problems or with economic objectives.